CONSUMER PROTECTION MEASURES FOR ERRONEOUS OR UNAUTHORIZED INTERNET PAYMENTS: SOME LESSONS FROM THE EUROPEAN UNION? - Vivienne A Lawack-Davids; Frans E Marx (Obiter, 2021)
The increase in cyber malls or internet shops presents consumers with a magnitude of goods, including digitized goods and information to choose from. In purchasing these commodities, the internet, in particular, offers the consumer various payment possibilities, such as credit card and online fund transfers to third parties. However, these payment instruments are not flawless. Errors may occur whilst the consumer is making such payment, the system may malfunction or unauthorized payments may be made.The aim of this analysis is to ascertain whether the existing law has measures that would be wide enough to protect a consumer in these instances. The position in South Africa is evaluated against this background and compared with the position in the European Union.